Recall the rules for the cross product:
i x i = j x j = k x k = 0
i x j = k
j x k = i
k x i = j
For any two vectors a and b, we also have anticommutativity:
a x b = -(b x a)
(a) A = 2.0 i - 4.0 j + k, C = 3.0 i + 4.0 j + 10.0 k
A x C = 6.0 (i x i) - 12.0 (j x i) + 3.0 (k x i)
.......... + 8.0 (i x j) - 16.0 (j x j) - 4.0 (k x j)
.......... + 3.0 (k x i) + 4.0 (k x j) + 10.0 (k x k)
A x C = (4.0 + 4.0) i + (3.0 - 3.0) j + (12.0 + 8.0) k
A x C = 8.0 i + 20.0 k
With the same steps as in (a), we get
(b) A x C = 44.0 i + 17.0 j - 20.0 k
(c) A x C = -24.0 k
(d) A x C = -(C x A) = -18.0 i - 18.0 k